Comparative effect of fixed-dose combination tablets of candesartan cilexetil/amlodipine versus olmesartan medoxomil/azelnidipine on laboratory parameters in patients with hypertension: a retrospective cohort study. (17th February 2016) - Susa, Norio; Nishida, Yayoi; Yada, Yoichi; Nakayama, Tomohiro; Asai, Satoshi; Takahashi, Yasuo
Abstract: We conducted a retrospective cohort study to evaluate and compare the long-term effects of two single-pill fixed-dose combinations (FDCs), candesartan/amlodipine and olmesartan/azelnidipine, on laboratory parameters in patients in routine clinical practice. We identified an equal number of new users ( n  = 182) of a candesartan/amlodipine (8/5 mg/day) FDC tablet (CAN/AML users) and a propensity-score matched cohort ( n  = 182) receiving an olmesartan/azelnidipine (20/16 mg/day) FDC tablet (OLM/AZ users). Generalized estimating equations were used to estimate and compare the effects of the drugs on serum levels of creatinine, estimated glomerular filtration rate (eGFR), blood urea nitrogen (BUN), uric acid, sodium, potassium, aspartate aminotransferase, and alanine aminotransferase levels up to 12 months after the start of study drug administration. There was a significant increase of serum creatinine level and a significant decrease of eGFR from the baseline period to during the exposure period in both CAN/AML and OLM/AZ users, and a significant increase of BUN level in CAN/AML users. However, there were no significant differences in the mean changes of laboratory parameters between CAN/AML and OLM/AZ users. Our findings suggested that the effects of CAN/AML and OLM/AZ on laboratory parameters, including an unfavorable effect on renal function, were similar at least during 1 year of administration.